Fast monostatic radar cross‐section computation for perfectly electric conducting targets using low‐rank compression and adaptive integral method. Issue 1 (1st January 2014) - Lü, Zhi‐Qing; An, Xiang
Abstract : The adaptive integral method (AIM) in conjunction with the low‐rank compression method is developed to calculate the monostatic radar cross‐section (RCS) of arbitrarily shaped three‐dimensional perfectly electric conducting objects. For backscattering problems, the excitation matrix is usually highly rank‐deficient and can be compressed via low‐rank techniques without explicitly assembling the original matrix beforehand. Therefore, only the matrix equations corresponding to the linearly independent excitation vectors need to be solved, whose number is much less than that of incident angles. As a result, fast monostatic RCS calculation over a widely angular range can be achieved. To facilitate the analysis of electrical large problems, the AIM is applied to accelerate the matrix–vector product and reduce the memory usage. Numerical examples are presented to demonstrate the validity and efficiency of the method.